HYPOMORPHIC OVARIES IN METAPENAEUS MONOCEROS (FABRICIUS) - Nalini, C (Indian Journal of Fisheries, 2011)
The hypmaorpibic ovaries in three specimens of Metapenaeus monoceros(Fabrictns) obuuaed from Cochin waters during November 1973, are described. Theabnormalities noticed pertain to the relatively undevelc^d state of the posteriorlobe of the ovary in two specunens, and of the proximal ith region of the anteriorlobe in a third one. Tbe probable causes for such aboormal development of theovary are discussed.